Changes in facial morphology after adenotonsillectomy in mouth-breathing children - Mattar, Sara E. M.; Valera, Fabiana C. P.; Faria, Gisele [UNESP]; Matsumoto, Miriam A. N.; Anselmo-Lima, Wilma T. (Wiley, 2011)
Background. Morphological and dentofacial alterations have been attributed to impaired respiratory function. Objective. To examine the influence of mouth breathing (MB) on children facial morphology before and after adenoidectomy or adenotonsillectomy. Methods. Thirty-three MB children who restored nasal breathing (NB) after surgery and 22 NB children were evaluated. Both groups were submitted to lateral cephalometry, at time 1 (T1) before and at time 2 (T2) 28months on average postoperatively. Results. Comparison between the MB and NB groups at T1 showed that mouth breathers had higher inclination of the mandibular plane; more obtuse gonial angle; dolichofacial morphology; and a decrease in the total and inferior posterior facial heights. Twenty-eight months after the MB surgical intervention, they still presented a dolichofacial morphologic pattern. During this period, MB altered the face growth direction and decreased their mandible plane inclination, with reduction in the SN.GoGn, PP.MP, SNGn, and ArGo.GoMe parameters as well as an increase in BaN.PtGn. Conclusion. After the MB rehabilitation, children between 3 and 6years old presented significant normalization in the mandibular growth direction, a decrease in the mandible inclination, and an increase in the posterior facial height. Instead, they still persisted with a dolichofacial pattern when compared with nasal breathers. © 2011 The Authors. International Journal of Paediatric Dentistry © 2011 BSPD, IAPD and Blackwell Publishing Ltd.
Keywords: adrenalectomy; case control study; cephalometry; face; growth, development and aging; histology; human; mandible; maxillofacial development; mouth breathing; nonparametric test; nose obstruction; pathology; pathophysiology; preschool child; tonsillectomy; tooth occlusion; Adrenalectomy; Case-Control Studies; Cephalometry; Child, Preschool; Face; Humans; Mandible; Maxillofacial Development; Mouth Breathing; Nasal Obstruction; Statistics, Nonparametric; Tonsillectomy; Vertical Dimension